2015
DOI: 10.3390/met5010070
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Spark Plasma Sintered Aluminum Containing 1 wt.% SiC Nanoparticles

Abstract: Abstract:The low hardness and strength of aluminum, which limits its use in many industrial applications, could be increased through the addition of nanoparticles. However, the appropriate processing method and parameters should be carefully selected in order to achieve the desired improvement in properties. In this work, aluminum was reinforced with low weight fraction (1 wt.%) of SiC nanoparticles and consolidated through spark plasma sintering. The effect of processing parameters on the densification, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…The hardness value is attributed to higher density value. Similar studies were reported [30][31][32][33][34]. It was reported that increase in the sintering temperature reduces the amount of large pores and also reduce grain size indeed increases density.…”
Section: Walsupporting
confidence: 82%
“…The hardness value is attributed to higher density value. Similar studies were reported [30][31][32][33][34]. It was reported that increase in the sintering temperature reduces the amount of large pores and also reduce grain size indeed increases density.…”
Section: Walsupporting
confidence: 82%
“…The ratio between Al 2 O 3 and Al can be obtained from the XRD using the relative intensities of Al 2 O 3 peak at 2θ=15.9 o (Al 2 O 3 phase) 26 and Al peak at 2θ=38.2 o (111 plane). 27 The AC-Al shows a higher Al 2 O 3 content of about 14.6% as compared with that of the AC-GP, indicating the graphite layer can reduce the Al 2 O 3 lm formation. Note, the Al 2 O 3 lm spontaneously grows on the Al foil surface at atmospereic condition having humidity.…”
Section: Main Textmentioning
confidence: 90%
“…Powder metallurgy (PM) technology has been of interest to several industrial sectors for decades. The necessity for metallic materials with improved mechanical and physical properties to satisfy the current requirements has resulted in development of new manufacturing processes [ 1 , 2 ]. The AA7075 aluminum alloy is widely used in the aeronautical, marine, automotive and defense industries for its high mechanical strength to weight ratio [ 3 , 4 ], but is still the subject of several studies seeking to further improve its mechanical properties [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The manufacture of aluminum alloy parts commonly uses powder metallurgy processes, such as cold isostatic pressing (CIP), hot isostatic pressing (HIP), hot pressing (HP), hot extrusion and hot rolling. These are competitive with respect to casting and extrusion, but it involves the degassing of the powder for several hours and several more hours (1–5 h) at relatively high temperatures [ 6 , 7 ], which makes the process expensive [ 1 , 2 , 8 ]. Moreover, the long cycle time and high temperatures lead to the growth of the grains, to the detriment of the final properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation